2006
DOI: 10.1159/000097097
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of Cognitive Function in Older Adults by Clock Drawing, Box Copying and Narrative Writing

Abstract: Objective: To examine 3 cognitive screening tasks in older adults and determine which demographic, medical and lifestyle variables obtained 13–17 years previously predicted cognitive performance. Design: Population-based longitudinal cohort study begun in 1981. Setting: Leisure World Laguna Hills, a California retirement community. Participants: The cohort is predominantly white, well educated, upper-middle class; two thirds are women. Data from 1,744 participants (mean age 83 years, range 57–103) were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 88 publications
2
13
0
Order By: Relevance
“…However, these studies do not, unlike ours, demonstrate the influence of age or education on CDT scores. Interestingly, there was a positive association between CDT performance and education in the above-mentioned studies on subjects belonging mainly to the well-educated upper-middle class [5, 8]. In another study, higher sensitivities and lower specificities were observed among those 85 years old and above as compared with those in other age groups [1], which is in keeping with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, these studies do not, unlike ours, demonstrate the influence of age or education on CDT scores. Interestingly, there was a positive association between CDT performance and education in the above-mentioned studies on subjects belonging mainly to the well-educated upper-middle class [5, 8]. In another study, higher sensitivities and lower specificities were observed among those 85 years old and above as compared with those in other age groups [1], which is in keeping with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Our study suggests that this procedure is an oversimplification, and that CDT performance should be interpreted according to a subject’s age and education. This suggestion corroborates the finding that both age and education emerged as predictors of CDT performance in studies on both the normal elderly [1, 2, 5] and impaired populations, such as those hospitalized for rehabilitation following stroke or a hip fracture [18]. However, these studies do not, unlike ours, demonstrate the influence of age or education on CDT scores.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations